Dancing with crime caught in the menacing net of London's underworld - Wyer, Reginald H. 1901-1970; Attenborough, Richard 1923-2014; Barnes, Barry K. 1906-1965; Sim, Sheila 1922-2016 (Cohen Film Collection, 2013)
"When childhood friends and army comrades Dave Robinson (Bill Rowbotham) and Ted Peters (Richard Attenborough) return home from WWII, they make very different choices for their new civvy lives. Ted gets an honest job as a taxi driver, and saves for his wedding to childhood sweetheart Joy (Sheila Sim). Dave, however, wants easy cash and soon becomes involved with a gang. When Dave runs into money troubles with the mob boss, a henchman is sent to finish him off. Stumbling from his gun wounds, he seeks shelter in the back of Ted's empty taxi and collapses, lifeless. Suspicions fly as Scotland Yard investigates the murder. The police suspect Dave's underworld connections. The mob suspects the Ted knows their guilt. And Ted himself suspects who the real killer might be... Set in London, this riveting crime drama has its roots firmly in the American gangster films of the 1930s - a must watch for genre lovers."
Bildformat 4:3
Original ©1947 Paramount Pictures
"Cohen Media Group presents a new 2K restoration of Dancing with crime from Cohen Film Collection in conjunction with the British Film Institute"
Verlagsnummer 139263
Keywords: Film noir; Crime films; Feature films; Fiction films; Film; DVD-Video